2015
DOI: 10.1007/s10552-015-0574-8
|View full text |Cite
|
Sign up to set email alerts
|

Trends in initial management of prostate cancer in New Hampshire

Abstract: There are encouraging trends in the management of clinically localized prostate cancer in New Hampshire, including less aggressive treatment of low-risk cancer and increasing surgical treatment of high-risk disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 23 publications
2
14
0
Order By: Relevance
“…Interestingly, though, more recent year (post‐2006) diagnoses were associated with higher likelihood of single‐trip intervention, which largely represented surgery. This reflects our recent findings, published separately, that surgical intervention has become significantly more common for all risk categories in recent years in New Hampshire, likely because of changing treatment paradigms (ie, more aggressive use of surgery for higher‐risk cancer) and the advent of robotic surgery to the state . Finally, “married” status was associated with XRT; speculatively, it may be that those who are married have greater logistical support for daily treatments.…”
Section: Discussionsupporting
confidence: 65%
“…Interestingly, though, more recent year (post‐2006) diagnoses were associated with higher likelihood of single‐trip intervention, which largely represented surgery. This reflects our recent findings, published separately, that surgical intervention has become significantly more common for all risk categories in recent years in New Hampshire, likely because of changing treatment paradigms (ie, more aggressive use of surgery for higher‐risk cancer) and the advent of robotic surgery to the state . Finally, “married” status was associated with XRT; speculatively, it may be that those who are married have greater logistical support for daily treatments.…”
Section: Discussionsupporting
confidence: 65%
“…This decline likely comes from the decreasing cebp.aacrjournals.org Downloaded from incidence of prostate cancer, which mostly reflects changes in prostate-specific antigen (PSA) screening (13,14). In addition, changes in patterns of treatment including more men choosing active surveillance may reduce the number of men undergoing radiation therapy (15,16). The landscape of prostate cancer survivorship may continue to evolve with the recently published PROTECT study that found similar cancer-specific survival among active surveillance, surgery, and radiation in earlystage prostate cancer (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…This use of active surveillance is substantially higher than that reported in the United States. 1,9,10 Potential facilitating factors for the rapid uptake of active surveillance in Sweden include 2007 national guidelines recommending active surveillance for men with low-risk prostate cancer and a life expectancy of 10 to 20 years. In 2014, the 20-year upper limit for life expectancy was abandoned, and active surveillance was recommended for all men with very-low-risk prostate cancer.…”
Section: Brief Reportmentioning
confidence: 99%